An analysis of hospital service quality by applying the fuzzy-promethee method - Angga Rusdi; Firman (Universitas Negeri Padang, 2021)
This study will only focus on the external side of the hospital, namely from the point of view of patients who use services at the hospital, especially on services during inpatient visits, which are delivered through the available suggestion box. The collection method in this study used observation, interviews, and questionnaires. In this study, the researcher used the servqual method and the fuzzy Promethee ranking to measure the quality of service. The results of the research on the quality of service at the Prof. Dr. MA Hanafiah Batusangkar Regional Hospital are of the five criteria studied by the researchers, namely, tangible, reliability, responsiveness assurance, and empathy.